THE COOPERATIVE AND POLITENESS PRINCIPLES IN RADIO BROADCASTING CONVERSATIONS - Fizi, Ridhani (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2020)
Abstrak The conclusions are related to the two research problems: 1) The Extent of the Use of the CP and the PP in the English Broadcasting Conversations, The ten maxims of the CP and PP are applied in terms of the maxims observances. Their uses vary from the most to the least frequent used. It can be concluded that in carrying out conversations over telephone in MAS FM radio broadcast politeness or being civil turns out not to be as powerful and not as important as being cooperative since the focus is on the topic forwarded and not so much on politeness. Besides, it shows that there are a lot of overlapping and violating of the maxims. The most frequent violated is the Relation Maxim. It is reasonable because some audiences know the presenters, meaning they are regular audiences in the program. Since they are not newcomers in joining the program, they frequently make a mocking joke. Their conversations are even out of topic and prolix. Thus, an utterance could be analyzed based on various angles because it may contain several maxims based on various points of view. And 2) The Speakers Purposes in Terms of Illocutionary Acts (IA), From the four function of IA, the only function, which is not applied at all by the participants, is the Conflictive. The all sub functions: threatening, accusing, cursing, and reprimanding cause conflicts among the participants in carrying out their conversa- tions. In fact, the participants in the radio broadcasting conversations try to avoid conflicts with others because in carrying out a conversation over the telephone is a non face-to-face conversation which is conduc- ted without facial expressions and gestures. Kata kunci : Cooperative Principle (CP), Politeness Principle (PP), Illocutionary Acts (IA), Conversations, Radio Broadcasting Program